Adopting and Adapting AI for EFL Teaching in Indonesian Higher Education - Hasanah, Uswatun; Jabu, Baso; Baa, Sultan (STAIN Majene, 2025)
Like a double-edged sword of technology, the swift development of Artificial Intelligence (AI) in English Language Teaching (ELT) has generated both benefits and drawbacks. While AI offers efficiency, personalization, and diverse learning resources, its integration requires critical consideration of pedagogical, ethical, and contextual factors. This study investigates how EFL educators in Indonesian higher education perceive, adopt, and adapt AI tools in their teaching, focusing on acceptance, practical use, perceived risks, and training needs. This study applied a qualitative case study approach, in which five lecturers with previous experience in using AI for language teaching were interviewed through a semi-structured format. The collected data were examined using thematic analysis, guided by the Technology Acceptance Model (TAM) and the framework of professional development theory. Findings reveal varied acceptance levels, such as some educators demonstrate a high adoption tendency, others adopt it selectively to align with pedagogical goals, and some engage in critical adoption with verification. Reported benefits include time savings in material preparation, enhanced engagement, and increased flexibility., Meanwhile, concerns involve content accuracy, over-reliance by students, reduced teacher–student interaction, and uneven digital infrastructure. Most participants expressed the need for targeted, practice-oriented training, particularly in designing AI-assisted learning media. The research highlights that institutional support, clear ethical frameworks, and continuous professional training are essential to guarantee that AI functions as a supportive tool rather than substituting teachers’ expertise. Beyond highlighting varied adoption tendencies and training needs, this study informs the development of professional development programs and ethical guidelines tailored to the realities of Indonesian higher education. While the study is limited to a small number of lecturers in a single context, it opens pathways for comparative and longitudinal research that can further enrich global understanding of AI integration in EFL education.